Taguchi-Grey method optimization of VCR engine performance and heat losses by using Shorea robusta biodiesel fuel - Kumar Rai R.; Rekha Sahoo R. (My University, 2025)
In the current investigation, biodiesel was produced via a single-stage transesterification method, from Shorea robusta seed oil and using KOH as a catalyst. Diesel based Shorea robusta biodiesel blends of SRME10, SRME20, SRME30, and SRME 40 were prepared, and its effect on the performance characteristics, emission attributes, and heat losses for the VCR engine were investigated. Experiments were designed using the Taguchi method with L16 orthogonal array, and the compression ratio, load, and % blends of fuel with four levels of each were taken as control parameters. Also, Grey analysis has been performed to obtain the combination of control parameters to optimize the response characteristics, i.e., brake mean effective pressure (BMEP), brake specific fuel consumption (BSFC), volumetric efficiency (ɳv), water heat loss (HJW), exhaust gas heat loss (HJGAS), NOx, HC and CO emissions. Experimental investigation and optimization analysis revealed that a compression ratio of 17, a load of 10 kg, and fuel blend of SRME30 were the optimum results for the performance and heat losses of the VCR engine. However, the comparative analysis, revealed that BTHE, BSFC, HGAS, and NOx emission enhances 9.4%, 10.71%, 14.16%, and 6.5% respectively, and HJW, HC and CO emission reduces 1.3%, 16.76%, and 21.2% respectively, for an optimum condition with respect to diesel fuel. The predicted GRG at an optimum setting (A3B4C3) and the experimental GRG value are 0.6896 and 0.7100, respectively, with an error of 0.0203. The experimental investigation confirmed that SRME30 could be used as an alternative to diesel fuel for the VCR engine. © 2020 Elsevier Ltd